Bridge to Terabithia - Paterson, Katherine; Diamond, Donna (New York : Crowell, 1977)
The life of a ten-year-old boy in rural Virginia expands when he becomes friends with a newcomer who subsequently meets an untimely death trying to reach their hideaway, Terabithia, during a storm.
Keywords: Friendship; Death